2020
DOI: 10.1101/2020.02.09.938993
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Both DNA binding domains of p53 are required for its ultra-rapid recruitment to sites of UV damage

Abstract: p53 concentrates at DNA damage sites within two seconds upon UV laser microirradiation. Structural analysis shows that this very rapid response requires both the DNA 15 binding and C-terminal domains of p53. This early recruitment response is also PARPdependent. As mutations within the DNA binding domain of p53, that are commonly associated with cancer also inhibit this rapid binding, we suggest that this is an important initial step for p53 function as a tumor suppressor. 20 One Sentence Summary: p53 is an ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…TP53 mutations in human cancers exhibit diverse functional consequences including loss- and gain-of-function 17 and almost invariably display abnormal DNA binding and transcriptional properties 18 . A recent study reported rapid PARP-dependent recruitment of p53 to sites of DNA damage that required the DNA binding and carboxyl terminal domains of p53 19 . We therefore assayed the production of pRPA32 foci upon si ENDOD1 in a range of cell lines with defined TP53 mutations.…”
Section: Resultsmentioning
confidence: 99%
“…TP53 mutations in human cancers exhibit diverse functional consequences including loss- and gain-of-function 17 and almost invariably display abnormal DNA binding and transcriptional properties 18 . A recent study reported rapid PARP-dependent recruitment of p53 to sites of DNA damage that required the DNA binding and carboxyl terminal domains of p53 19 . We therefore assayed the production of pRPA32 foci upon si ENDOD1 in a range of cell lines with defined TP53 mutations.…”
Section: Resultsmentioning
confidence: 99%